The future treatment for type 1 diabetes: Pig islet- or stem cell-derived β cells? - Naqvi, Raza Ali; Naqvi, Afsar Raza; Singh, Amar; Priyadarshini, Medha; Balamurugan, Appakalai N.; Layden, Brian T. (Frontiers in Endocrinology, 2023)
Replacement of β-cells is only curative approach for type 1 diabetes (T1D) patients to avoid the threat of iatrogenic hypoglycemia. In this pursuit, islet allotransplantation under Edmonton’s protocol emerged as a medical miracle to attain hypoglycemia-free-insulin independence in T1D. Shortage of allo-islet donors and post-transplantation (post-tx) islet loss are still unmet hurdles for the widespread application of this therapeutic regimen. Long-term survival, and effective insulin independence in preclinical studies has strongly suggested pig islets to cure overt hyperglycemia. Importantly, CRISPR-Cas9 technology is pursuing to develop ‘humanized’ pig islets that could overcome the lifelong immunosuppression drug regimen. Of late, induced pluripotent stem cells (iPSCs) derived β-cell approaches are also gaining momentum and may hold promise to yield significant supply of the insulin producing cells. Theoretically, personalized β cells derived from patient’s iPSCs is one exciting approach, but β-cell specific immunity in T1D recipients would still be a challenge. In this context, encapsulation studies on both pig islet as well as iPSC- β-cells was found promising and rendered long-term survival in mice. Oxygen tension and blood vessel growth within the capsules are few of the hurdles that need to be addressed. In conclusion, challenges associated with both procedures, xenotransplantation (of pig-derived islets) and stem cell transplantation are required to be cautiously resolved before their clinical application.